ANALISIS KUALITAS PELAYANAN PENGADUAN MASYARAKAT DI DINAS PENDIDIKAN KABUPATEN SUMEDANG - Sudrajat, Arip Rahman; Rahman, Ade Opik; Erlanda, Agussyahrul Noer; Darmawan, M. Ilham; Zahira, Nadia Marsa; Nabila, Nazwa; Fatimah, Zahra Aulia (JRPA - Journal of Regional Public Administration, 2024)
This study aims to determine how the quality of service in public complaints at the Sumedang Regency Education Office, knowing the government's obstacles in achieving service quality in managing public complaints and the efforts made by the government in managing public complaints at the Education Office. This study was conducted using a qualitative approach. Observation, interviews, triangulation and documentation studies were the methods used in data collection. This study, using data analysis, concluded that the quality of service regarding public complaints at the Sumedang Regency Education Office is quite good. Based on the obstacles contained in the quality of public complaints, there are no significant obstacles found, only a lack of responsiveness, and community participation. However, all of that can be overcome well by service implementers. Efforts in overcoming these obstacles include: Good socialization to the community regarding the quality of online-based services so that people understand the existence of online service complaints. So that the quality of service regarding complaints at the Sumedang Regency Education Office matches what is needed.